Analisis Pelatihan Kerja, Kemampuan Kerja, dan Disiplin Kerja terhadap Quality of Work Life di PT. Sansan Saudaratex Jaya 8 - Diana Riski Puspitasari; Kusuma Chandra Kirana; Didik Subiyanto (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study purpose of analyze and test the variables of job training, work ability, and work discipline on the quality of work life in the company. This study has a population and a sample of 53 obtained from PT. Sansan Saudaratex Jaya 8. This study used a quantitative method with the help of the SPSS version 28 program. These data were obtained from primary sources, namely by distributing questionnaires that were created using Google from and distributed online. After obtaining these data, they were analyzed using descriptive analysis and multiple linear regression analysis. To find out the results of the hypothesis in this study, the hypothesis was tested using the t test, f test and also the coefficient of determination (R2). After the data processed in this research, job training has a positive and significant relationship to the quality of work life. Work ability has a non-positive and insignificant relationship with the quality of work life. Work discipline has a positive and significant relationship to the quality of work life. And the last job training, work ability and work discipline shows the results that have a positive and significant relationship simultaneously to the quality of work life at PT. Sansan Saudaratex Jaya 8. Keywords: Job training, Work ability, Work discipline, Quality of work life.